Understanding Latin America and the Caribbean’s Income Gap - Thompson Araujo, Jorge; Vostroknutova, Ekaterina; Wacker, Konstantin M.; Clavijo, Mateo (World Bank, Washington, DC, 2015)
Even nearly ten years of solid growth cannot guarantee long-term income convergence. The countries of the Latin America and Caribbean region (LAC), like other emerging economies, have benefited from a decade of remarkable growth and some income per capita convergence towards the United States and other industrialized countries. Yet, despite this recent progress, LAC still faces a significant per capita income gap with the developed world. The studies in this volume contribute to the ongoing debate on the reasons for this persistent income gap and the potential drivers of convergence, and propose some broad avenues for reform.